MENINGKATKAN AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) MENGGUNAKAN COOPERATIVE LEARNING TIPE STAD PADA SISWA KELAS V SDN NO. 12 NUSA PANDAU TAHUN 2011/2012 - Diana, Diana; Mardiana, Mardiana; Haryadi Saputra, Eko Feri (JURNAL PENDIDIKAN DASAR, 2014)
The purpose of this research is to increase the student learning activity on subject Natural Science by using cooperative learning model of STAD type. The instrument used was the evaluation sheets: student assignment sheet and trial or experiment sheet. This action research was done in 2 cycles. In the pre-cycle showed that from the 16 students, there were 32% students who were passed the subject, where then in the first cycle it was increased to 62.50% and 81.25% in the second cycle. In addition, the students were looking more enthusiasts in doing the given experiment. It was shown that each group helps each other and became more responsible on their task. Therefore, this cooperative model by STAD type was able increase the student learning activity, especially on the subject Natural Science. Keywords: Activity, Natural Science Learning, Cooperative Learning Model of STAD type